A Facile Strategy to Support Palladium Nanoparticles on Carbon Nanotubes, Employing Polyvinylpyrrolidone as a Surface Modifier. Issue 9 (March 2014) - Cardoso, Mariana B. T.; Lewis, Edward; Castro, Pollyana S.; Dantas, Luiza M. F.; De Oliveira, Caio C. S.; Bertotti, Mauro; Haigh, Sarah J.; Camargo, Pedro H. C.
Abstract: Invited for the cover of this issue is the group of Pedro Camargo at the University of São Paulo, Brazil, collaborating with the group of Sarah Haigh at the University of Manchester, UK. The cover image shows the deposition of palladium nanoparticles (Pd NPs) on the surface of carbon nanotubes (CNTs) by a simple strategy employing ethanol as the solvent/reducing agent, potassium tetrachloropalladate(II) (K2 PdCl4 ) as the Pd precursor, and polyvinylpyrrolidone (PVP) as the surface modifier. Abstract : We are fascinated with the possibility of using simple chemistry to develop strategies that enable precise control over size, shape, structure, and even composition for multimetallic systems... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 1439 ff .